24x - 6x (13x -9)= -13- 13x (6x - 1).​

снежана183 снежана183    3   10.03.2021 19:12    0

Ответы
viktr1 viktr1  10.03.2021 19:20

x=-1/5 или x=-0,2

Объяснение:

на фотографиях

♡♡♡♡♡♡♡♡


24x - 6x (13x -9)= -13- 13x (6x - 1).​
24x - 6x (13x -9)= -13- 13x (6x - 1).​
ПОКАЗАТЬ ОТВЕТЫ
exomashka exomashka  10.03.2021 19:20

24x - 6x (13x -9)= -13- 13x (6x - 1)

24x-78x²+54=-13-78x²+13x

24x-78x²+78x²-13x=-54-13

24x-13x=-67

11x=-67

x=-67:11

x=-6,(09) либо дробью -67/11 = - 6 целых 1/11

ответ:-6, (09)

ПОКАЗАТЬ ОТВЕТЫ